Pengaruh Periklanan, Kemudahan Penggunaan Dan Kepercayaan Masyarakat Terhadap Perilaku Niat Menggunakan Kontrasepsi (Studi Pada Peserta KB Aktif Di Kec. Wangi-Wangi Kab. Wakatobi) - Hasmawati Hasmawati; Nasrul Nasrul; Nursaban Rommy Suleman; Patwayati Patwayati (Pascasarjana Universitas Halu Oleo, 2022)
The purpose of this study was to examine the effect of advertising, ease of use and trust on the behavior of intention to use contraceptives in active family planning participants, Wangi-Wangi District, Wakatobi Regency. The population in this study were all users of contraceptive devices, namely 3637 people. The number of samples determined was 75 contraceptive users in Wangi-Wangi District, Wakatobi Regency, the data from the sample/respondent were analyzed using SmartPLS in order to obtain the results of the causal relationship between the variables developed in the model. The results of testing advertising, ease of use and public trust in the behavior of intention to use contraceptives in active family planning participants, Wangi-Wangi District, Wakatobi Regency, are as follows; the effect of advertising on the behavior of intention to use contraceptives has a path coefficient of 0.300 with a probability level of 0.022 (p <0.05), the effect of ease of use on the behavior of intention to use contraceptives has a path coefficient of 0.318 with a probability level of 0.012 (p < 0, 05), the effect of ease of use on behavioral intention to use contraceptives has a path coefficient of 0.197 with a probability level of 0.134 (p > 0.05). The benefit that can be learned from this research is the development of knowledge, especially in the paradigm of structural relationship of advertising, ease of use and public trust in the behavior of intention to use contraceptives.